Optimization of working parameters for puddling and flatting machine in paddy field - Chunlin, Xu; Chengliang, Zhang; Lianhao, Li; Mingjin, Li (International Journal of Agricultural and Biological Engineering, 2016)
In order to improve the soil preparation quality, a wide puddling and flatting machine for paddy field was designed with the functionality of tillage, soil crushing, puddling, burying stubble and flatting in one-time operation, which can be equipped on tractors with high power. This study focused on the design and analysis of key components of the machine including puddling equipment, flat shovel and balance structure. Optimal results with field trials and response surface analysis showed that the machine can operate optimally when the working speed, puddling depth and angle of flat shovel were 1.05 km/h, 16 cm and 31.30°, respectively. The surface flatness standard deviation was 3.7 cm, and slurry degree was 1.03 g/cm3. Field validation test results were consistent with the optimal parameters, which was able to meet agronomic requirements of mechanical planting in China. Keywords: paddy field, puddling and flatting machine, rice production, design, field test, optimization DOI: 10.3965/j.ijabe.20160903.1608 Citation: Xu C L, Zhang C L, Li L H, Li M J. Optimization of working parameters for puddling and flatting machine in paddy field. Int J Agric & Biol Eng, 2016; 9(3): 88－96.